2018
DOI: 10.1161/circheartfailure.117.004325
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Assist Device Inflow Cannula Angle and Thrombosis Risk

Abstract: Angulation of the inflow cannula >7° from the apical axis (axis connecting mitral valve and ventricular apex) leads to markedly unfavorable hemodynamics as determined by computational fluid dynamics. Computational hemodynamic simulations incorporating Lagrangian and Eulerian metrics are a powerful tool for studying optimization of LVAD implantation strategies, with the long-term potential of improving outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 32 publications
4
80
0
Order By: Relevance
“…Other authors have also implicated LV size and devicerelated factors as important for pump thrombosis, and these factors would not necessarily be addressed with current surgical strategies for pump exchange. [25][26][27] Our own results lend credence to this theory.…”
Section: Discussionsupporting
confidence: 77%
“…Other authors have also implicated LV size and devicerelated factors as important for pump thrombosis, and these factors would not necessarily be addressed with current surgical strategies for pump exchange. [25][26][27] Our own results lend credence to this theory.…”
Section: Discussionsupporting
confidence: 77%
“…To date, the effect of inflow cannula malposition in the left ventricle (LV) has been identified as an important component associated with thrombosis in LVAD patients. [24][25][26][27] On the other hand, no studies have specifically addressed the prothrombotic interplay between LV cannulation and residual contractility of the pathologic heart failure LV. We developed a computational platform to characterize patient-specific intraventricular hemodynamics in the LVAD-implanted LV, accounting for potential mechanisms related to thrombus formation as a consequence of limited ventricular contractility.…”
Section: Prothrombotic Hemodynamic Conditions In the Lvad-implanted Lmentioning
confidence: 99%
“…Non-physiological flow patterns in LVAD patients and abnormal stagnation areas within the ventricle were previously identified in experimental flow models, 22,23 in CFD models. 2426 However, since there is no clinical method applicable for LVAD patients to visualize the ventricular flow fields, in-vitro experiments and numerical simulations are still important tools for gaining insights into the flow patterns with specific limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation of the intraventricular flow field has been performed with the LAM method. 24,26 However, the FDA nozzle study identified issues for Re numbers larger than 500 in predicting main flow features downstream of an expansion. 15 Due to the highly dynamic flow already at the mitral inflow into the LV, it is impossible to identify one method that perfectly fits.…”
Section: Discussionmentioning
confidence: 99%